Hybrid silver-graphene nanoparticles enhanced Lauric Acid phase change material for photovoltaic and thermoelectric generator applications: Experimental and simulation analysis - Bhutto, Yasir Ali; Pandey, A. K.; Saidur, R.; Rathore, Pushpendra Kumar Singh; Mahendran, Samykano (Elsevier Ltd, 2024)
The global initiatives for renewable energy promote sustainable energy technologies such as photovoltaic thermal (PVT) systems and thermoelectric generators (TEGs). Latent heat energy storage is an effective method for conserving excess thermal energy and can be applied to PVT and TEG technologies. The fatty acid phase change materials (PCMs) are appealing, but their low thermal conductivity limits their practical usage. In this study, silver (Ag) and graphene (Gr) hybrid nanoparticles (NPs) are considered as additives to augment thermo-physical properties of lauric acid (LA) PCM for implementation in PVT and TEG applications. The nanocomposites are prepared by two-step technique. Additionally, implementation of composites in PVT has been evaluated experimentally and through TRNSYS simulation. Besides, composites impact on TEG application was assessed experimentally. As per results, photo-absorption analysis; nanocomposite LAG-3.5 (LA with 3.5 % hybrid Ag and Gr NPs) displayed the highest 76 % decrease in transmissibility. In addition, LAG-3.5 nanocomposite augmented thermal conductivity of LA by 57 % due to integration of high thermally conductive hybrid NPs. Further, LAG-3.5 composite reported an 8 % increment in latent heat enthalpy. As per reliability, after 500 thermal cycles, nanocomposite LAG-3.5 showed chemical stability and thermal durability. Moreover, optimal composite LAG-3.5 exhibited enhanced electrical characteristics while implementing in photovoltaic and thermoelectric generator application. Therefore, the nano-enhanced composite can be significant application prospects in the 45 °C to 50 °C melting temperature range.